Bereavement in children : a school based intervention programme - Feigenbaum, Pat (Division of Child and Adolescent Psychiatry, 2017)
The consequences of childhood bereavement are two-fold, in the pain he/ she suffers at the time of the death, and in future psychiatric disorders which can follow unresolved mourning. The bereaved child needs a familiar and responsible adult outside the family to help him/her cope with his/her grief, because parents are sometimes emotionally absent from him/her due to their own grief or they seek to "protect" the child from the pain of the loss. This study presents a programme given to 164 primary school teachers from nine schools in Cape Town to educate them in how to help the bereaved child in the classroom situation, so that they can fill the role of an outside responsible adult in the life of the bereaved child. 78 bereavements occurred in the nine schools in the year of the study. It was found that the teachers responded positively to the training programme and that they perceived it to be helpful in dealing with a bereaved child.